Pengaruh Promosi Penjualan Harbolnas Marketplace Terhadap Perilaku Konsumtif Generasi Milenial Di UBSI - Andriana, Dina; Martana, I Ketut; Baskoro, Angga Pradipta (KOMUNIKATA57, 2020)
The phenomenon of Harbolnas sales promotion is the latest trend in online retail. All circles are tempted to participate in the Harbolnas sales promotion program which is held annually on 12 December. This study focuses on how much influence the Harbolnas advertising campaign through the smartphone marketplace application has on the consumptive behavior of the millennial generation. The research method is carried out quantitatively, is explanatory with purposive sampling technique on 400 respondents at Bina Sarana Informatika University. The results of the study found that 1% of the additional use of factors in the sales promotion variable had a positive effect on increasing 0.326 consumptive behavior with the regression equation Y = 30.610 + 0.326X.